Effect of drought on agronomic characteristics and proteome patterns of selected Sabah dryland paddy varieties - Poey, Shao Jiann (2016)
Drought is the major limiting factor to paddy production worldwide. Thus, drought tolerance emerges as one of the most important aspects of paddy breeding programs. A study on Sabah's local dryland paddy varieties were carried out using Silabukan soil as planting medium at Faculty of Sustainable Agriculture, Universiti Malaysia Sabah. This study aimed to compare the agronomic characteristics between Beruang, Kelopak and Tiga Bulan dryland paddy varieties under normal and drought stress conditions. Two cycles of drought treatments were applied at 50% heading stage to agronomic replicates. Completely randomized design was used in this study. Results showed that early maturing Kelopak variety performed the best under normal condition, exhibited the highest extrapolated yield (4.856 tonnes ha-1). Drought stress at 50% heading stage led to a significant decrease in relative water content, percentage in filled grain and grain yield per plant. In this study, Tiga Bulan variety was the most drought-tolerant variety, which experienced the lowest percentage of yield reduction (28%) and gave the highest grain yield per plant (19.438 g plant1) under drought stress condition. Early flowering Tiga Bulan variety with slightly longer days to leaf rolling was selected for proteome analysis. Normal and completely rolled flag leaves of Tiga Bulan variety after first cycle of drought treatment at grain filling stage were subjected to Sodium Dodecyl SulphatePolyacrylamide Gel Electrophoresis (SDS-PAGE) analysis to compare their protein expressions. SDS-PAGE analysis revealed one and two bands were up- and downregulated significantly in response to drought respectively. These proteins may be involved in drought mechanism. Recent trend in climate change have predicted a further increase in drought intensity, therefore efforts to develop drought tolerant varieties are vital to sustain the paddy production worldwide.